TECHNOLOGY OF FORMATION AND DEVELOPMENT OF STUDENTS' INTELLECTUAL ABILITIES - Boyjigitov Shuhrat Absamatovich (Scholar Express Journal, 2022)
The end of XXI century the beginning of XXI century was a period of radical changes in the spiritual and material spheres of mankind. The wide range of innovative trends in socio-economic and socio-political development, changes in science, culture, ethics, aesthetics and other types of art that are taking place in the historical process have deeply affected and continue to exert influence. From such influences, the educational sphere is also not overlooked. It is predicted that the first decade of the 21st century and even then the material wealth will remain tied to the level of knowledge, experience, blindness, health, physical development. Consequently, science and culture holds an important role in ensuring the progress of every society. The experience of the world's leading countries is an example of this. After all, giving priority to education determines the prospects of the country and the people. In this article, opinions and comments are made about the technology of formation and development of students ' intellectual abilities
Keywords: Students; Intellektual Capacity; Higher Education; Teaching Methodology